Assessment of Challenges in Developing Self-Instructional Course Materials at the National Open University of Nigeria - Okonkwo, Charity Akuadi (International Review of Research in Open and Distributed Learning, 2012)
The National Open University of Nigeria (NOUN) is Nigeria’s only university dedicated to providing education through the use of distance instructional methods. So far, however, the lack of availability and poor distribution of course materials, which underpin instructional delivery at NOUN, continue to be hindrances to achieving the university’s vision and mission. There are delays and difficulties in developing and distributing materials to students and Study Centres. Many pioneer students cannot graduate because of this challenge. This paper examines the process of developing self-instructional course materials at NOUN. It reflects on the challenges associated with the quantity, quality, and timely production of course materials, labelled “the hills, the wills, and the skills” obstacles. The paper concludes that there is a need for better professional development in order to provide efficient ODL delivery.